Development Creativity Students through The Application of Problem Based Learning Model in Physical Education in Reviewed of Adversity Quotient - Setiawan, Edi; Juliantine, Tite (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2017)
The purpose of this research is to develop students' creativity through the application of problem based learning model in physical education in review of adversity quotient. The research method used is experimental method with 2x2 factorial designs. The population in this study are the students of 10th grade in SMK 1 Cipanas Cianjur Regency consists of 10th grade as many as 8 classes with a total of 375 students. The sample in this research is as many as 60 students, consists of 30 students with high adversity quotient skills and 30 students with low adversity quotient skills. The sampling using cluster random sampling technique. The instrument used is a questionnaire to measure the level of adversity quotient by Stolz (2000) and the creativity by Guilford (1950). The result of data analysis Two Way Anova showed that: (1) the development of students' creativity through problem based learning model is higher than direct instruction model. (2) There are differences of creativity between students who are given problem-based learning model and direct instruction model in groups of students who have high adversity quotient ability.(3)There are differences of creativity between students who are given problem-based learning model and direct instruction model in groups of students' who have low adversity quotient ability. (4) There are interactions between the learning model and the adversity quotient on students' creativity. The findings of this study confirmed that learning with problem based learning model gives more effective impact and can be applied by physical education teachers in an effort to develop student' creativity.